2019
DOI: 10.2169/internalmedicine.2415-18
|View full text |Cite
|
Sign up to set email alerts
|

Oral Anticoagulants in Japanese Patients with Atrial Fibrillation and Active Cancer

Abstract: Objective Oral anticoagulants (OACs), which include direct oral anticoagulants (DOACs) and warfarin, are widely used for the prevention of thromboembolic events in patients with atrial fibrillation (AF). Cancer is associated with a prothrombotic state as well as an increased bleeding risk. Few data are available on the efficacy and safety of OACs in Japanese cancer patients with AF. We sought to investigate the efficacy and safety of OACs in this population. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 18 publications
(19 reference statements)
1
37
0
Order By: Relevance
“…The more prevalent malignances across the studies were gastrointestinal, breast and prostatic cancers (Supplemental Material, Table S1). All the studies but three reported the propensity-score-matched or adjusted RRs [ 20 , 21 , 23 ] for pre-specified outcomes. In 7 out 9 studies, major bleedings were considered according to the ISTH criteria [ 24 ], whereas one study [ 20 ] reported any diagnosis of gastrointestinal, lung and urinary bleedings as safety outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The more prevalent malignances across the studies were gastrointestinal, breast and prostatic cancers (Supplemental Material, Table S1). All the studies but three reported the propensity-score-matched or adjusted RRs [ 20 , 21 , 23 ] for pre-specified outcomes. In 7 out 9 studies, major bleedings were considered according to the ISTH criteria [ 24 ], whereas one study [ 20 ] reported any diagnosis of gastrointestinal, lung and urinary bleedings as safety outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…After excluding duplicate publications, reviews, editorials, letters, meta-analysis, case reports and abstracts, 28 studies were fully reviewed and 9 studies were considered eligible for the meta-analysis. In particular, the studies used for the analysis included 3 post-hoc analysis from RCTs [14][15][16] and 6 retrospective population-based cohort studies [18][19][20][21][22][23] involving 46,424 DOACs users and 182,797 VKA users ( Table 1).…”
Section: Study Selection Quality Of Evidence and Patients Characterimentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, cancer patients have higher bleeding risks when treated with anti-thrombotic drugs for venous thromboembolism [6]. An increased risk of bleeding due to anticoagulation therapy with direct oral anticoagulants (DOAC) or warfarin has been reported [7][8][9][10][11]. Percutaneous coronary intervention (PCI) with stent implantation, which requires extended treatment with dualantiplatelet therapy (DAPT) followed by single-antiplatelet therapy (SAPT), is often performed as treatment for CAD in cancer patients.…”
Section: Introductionmentioning
confidence: 99%